Design and Implementation of an Automatic Rotating Paddy Drying System based on Microcontroller using Fuzzy Logic - Ramdani, Fadhil; Novani , Nefy Puteri (CHIPSET, 2026)
Rice production faces major challenges, notably unpredictable weather and pest attacks. The duration of sun drying depends on the climate and weather: if the weather is clear and the sun shines fully throughout the day, drying only lasts about 2–3 days. However, when the weather is occasionally cloudy or drizzly and sometimes hot, the drying time can extend to approximately one week. Pests such as birds cause significant physical damage to the paddy from pecking, which frequently occurs in conventional drying methods. The system design in this Final Project aims to design and build an automatic rotating paddy drying system that can control temperature and humidity using fuzzy logic. Fuzzy logic was chosen to adjust the drying temperature so that the resulting temperature is appropriate for the current paddy moisture, thereby maintaining paddy quality, operating independently of weather, and protecting against pests. The system utilizes an ESP32 microcontroller as the main processing unit. Input is obtained from a Capacitive Soil Moisture Sensor for paddy moisture and a DHT22 sensor for the drying chamber temperature. Fuzzy logic with 9 rules is implemented to control the Fan & Heater actuator based on the inputs from moisture and temperature. An AC motor with a gearbox is used to rotate the drying drum. The system is also integrated with a Telegram Bot for real-time monitoring and control. Testing was conducted in five weight scenarios ranging from 10 kg to 30 kg. The system successfully lowered the paddy moisture from the initial level to the drying target of 13%. The optimal capacity was identified at 10–20 kg, where the system was capable of maintaining the ideal temperature at 40°C–60°C. The system successfully controlled the drying process automatically, maintained temperature and humidity, and protected the paddy from contamination, resulting in a quality drying process.